Exploring student curiosity as a moderator in reward-based STAD for Pancasila education - Ni Putu Adi Utami; I Nengah Suastika; Desak Putu Parmiti (Research and Social Study Institute, 2025)
This qualitative case study investigates the moderating role of student curiosity in enhancing Pancasila learning outcomes through a Reward Management-Based Student Teams Achievement Division (STAD) Cooperative Learning Model in second grade. The research addresses the persistent challenge of low learning outcomes in the subject due to conventional teaching methods that limit student engagement. Aligned with the Merdeka Curriculum's emphasis on deep learning and holistic development , the study employed a qualitative methodology with data collected through in-depth interviews, participant observation, and document analysis. Findings reveal that the STAD model's structured implementation effectively transformed the learning environment, with both teachers and students reporting overwhelmingly positive experiences. Crucially, the reward management system was found to be a significant moderator that leveraged the students’ psychological need for recognition to foster a dynamic learning process. The study concludes that this synergy between the model, rewards, and curiosity is essential for achieving deeper, more meaningful learning in line with curriculum goals.